The Empathy Crisis in Digital Natives: The Relevance of KH. Ahmad Dahlan’s Al-Ma’un Theology in Contemporary Islamic Education - Nabila Raessal Manda Putri; Asa Mega Nusantara; Abdussyukur (AN NUR: Jurnal Studi Islam, 2026)
The development of digital technology has brought significant changes in the social interaction patterns of the digital-native generation, but it has also given rise to an empathy crisis characterized by a decline in social awareness, increased individualism, and shallow interpersonal relationships. This study aims to analyze the phenomenon of an empathy crisis among digital natives and examine the relevance of KH. Ahmad Dahlan's thoughts from the perspective of Al-Ma'un's theology as a solution in contemporary Islamic education. This study uses a qualitative approach with library research, through data collection from scientific journals, books, and relevant literature, analyzed using content analysis techniques. The results of the study indicate that the empathy crisis is not only influenced by the intensity of digital technology use, but also by the weak internalization of moral values ??and character in the education system. In this context, KH. Ahmad Dahlan's thoughts through Al-Ma'un's theology emphasize the importance of integrating faith, knowledge, and charity as a foundation for building social awareness. The implementation of these values ??in Islamic education can be done through strengthening moral education, developing individual rationality, and involvement in real social action. Thus, Islamic education in the digital era needs to be reoriented not only towards cognitive aspects, but also towards the formation of empathy and social responsibility in students, so that it can produce a humanistic and civilized generation.